KONTRIBUSI NILAI EKONOMIS LAHAN PEKARANGAN TERHADAP EKONOMI RUMAH TANGGA PETANI DI DESA RAMBAH SAMO KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - -, Marhalim (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2016)
Farm yards not only serves as an economic resource but also gives social contributions in the community and as a means of gathering among farmers in the District of Rambah Samo Rambah Rokan Hulu as well as a means of exchanging information about the farming they do. The purpose of this study was to determine the contribution of land use courtyard economic value tothe economy of the family. Techniques of data collection using surveys and interviews. Data analysis technique used is quantitative analysis. Results of the research farm yard area contributed revenue of Rp. 306.694 / planting period and accounted for 3.45% of the total receipts of the family.